Liver cirrhosis and complications from the perspective of dysbiosis - Nie, Guole; Zhang, Honglong; Xie, Danna; Yan, Jun; Li, Xun (Frontiers in Medicine, 2024)
The gut-liver axis refers to the intimate relationship and rigorous interaction between the gut and the liver. The intestinal barrier's integrity is critical for maintaining liver homeostasis. The liver operates as a second firewall in this interaction, limiting the movement of potentially dangerous compounds from the gut and, as a result, contributing in barrier management. An increasing amount of evidence shows that increased intestinal permeability and subsequent bacterial translocation play a role in liver damage development.. The major pathogenic causes in cirrhotic individuals include poor intestinal permeability, nutrition, and intestinal flora dysbiosis. Portal hypertension promotes intestinal permeability and bacterial translocation in advanced liver disease, increasing liver damage. Bacterial dysbiosis is closely related to the development of cirrhosis and its related complications. This article describes the potential mechanisms of dysbiosis in liver cirrhosis and related complications, such as spontaneous bacterial peritonitis, hepatorenal syndrome, portal vein thrombosis, hepatic encephalopathy, and hepatocellular carcinoma, using dysbiosis of the intestinal flora as an entry point.